Legal Implications of Defendant's Non-Compliance with Child Support Obligations Based on Ruling No. 214/Pdt.G/2023/PA.Gtlo - Laya, Putri Nadhia Diannita; Cherawaty Thalib, Mutia; Ahmad, Ahmad; Agustina, Ririn (Estudiante Law Journal, 2025)
This study aims to analyze the legal implications of the defendant's non-compliance with child support obligations and the judge's considerations in determining the amount and increase of child support in Decision No. 214/Pdt.G/2023/PA.Gtlo. The background of this research focuses on the issue of non-compliance with child support obligations after divorce, which often leads to negative impacts on the child's well-being and may trigger prolonged legal processes. In this context, it is important to explore how the law responds to such non-compliance and how judges consider various factors in determining fair and sustainable child support. The objective of this research is to examine the legal consequences of the defendant's non-compliance with child support obligations and to understand the basis of the judge's considerations in determining the amount and increase of child support, specifically the annual increase of 20%. The research method employed is empirical legal research with a qualitative approach, combining court decision document analysis and interviews with relevant parties. Primary data is obtained from interviews with judges and lawyers, while secondary data is gathered through relevant legal literature. The research results indicate that non-compliance with child support obligations may result in legal sanctions such as execution or fines, and impact subsequent legal processes. The judge's considerations in determining child support include the defendant's financial capacity, the child's needs, and the principle of social justice. A realistic decision on child support increases is essential for the sustainability of fulfilling the child's rights.